USULAN RUTE PENDISTRIBUSI MENGGUNAKAN ALGORITMA CLARKE AND WRIGHT SAVINGS DAN SEQUENTIAL INSERTION - Arif, Arif Chandra Setiawan; Suseno, Suseno (CV. ALIM'SPUBLISHING, 2024)
In this research, data was taken from the distribution route which was recorded by the cashier at the Cahaya Kristal Tube Ice Ice Factory which is located on Jl, Damai, Prujakan Tambakan Village, Sinduharjo, Ngaglik, Sleman Yogyakarta. Then the data is processed using the Clarke and Wright Savings Algorithm and Sequential Insertion with the aim of providing the best or most effective route suggestions and then comparing the two methods to produce the Travel Route Distance and Distribution Costs. By using the Clarke and Wright Saving Algorithm, we get 2 vehicle routes which produce a combined route of 72 km with a daily distribution cost of IDR 147,000, and for the sequential insertion algorithm method we also get 2 vehicle routes which produce a combined route of 107 km with a daily distribution cost of IDR 182,000. Thus it can be concluded that routes formed using the Clarke and Wright Savings Algorithm are more effective and economical compared to routes formed using the Sequential Insertion